Developing Intercultural Communicative Competence within the Framework of a University Language Course: The Case of a BA in English Studies Programme In Hungary - Talbi, Maroua (Working Papers in Language Pedagogy, 2020)
The present study focuses on the teaching of intercultural communicative competence (ICC) practices in tertiary education. The teaching of ICC tends to be overlooked by teachers of English as a foreign language (EFL), as they are more committed to teaching language than culture (Sercu et al., 2005). The present exploratory case study therefore seeks to describe and analyse how the ICC of English studies students is developed at BA level on the course “Communicating across cultures,” taught at a prestigious university in Hungary. It also explores good practices for developing the ICC of future EFL professionals in the same context. Systematic class observation and an analysis of the course reading materials were carried out to examine the features of ICC development on the course. These were followed by a semi-structured interview with the teacher, and a group interview with five students to examine their views on the course. The findings indicated that the students’ ICC was successfully developed on the course using both the target cultures and the students’ cultures. Moreover, cooperation among the students was found to be a central feature of this course, as it provided an opportunity for them to experience and discuss their intercultural interactions and thus develop their multiperspectivity. The examination of the teacher’s views revealed that he aimed both to raise the students’ awareness of cultural diversity and to develop their English language proficiency. His attitudes and teaching style may well have contributed to the student interviewees’ appreciation of this course. The case study introduces an example “of good practice” and shows that the approach and activities used on this course can be applied to the teaching of ICC when training future professional teachers of English in tertiary education programmes.